Determinants of Increasing Online Business Intentions through Locus of Control as a Mediating Variable in High School Students (a Study of High Schools in Banyuwangi District) - Amar Ma’ruf; Agus Hermawan; Nurika Restuningdyah (Formosa Journal of Applied Sciences, 2023)
This study was conducted to know the effect of entrepreneurship education, and self-efficacy on online business intentions through locus of control in vocational students in Banyuwangi. The urgency of this research lies in the great potential of using the internet and social media that can be utilized by the younger generation to start an online business. This research uses a quantitative method. The population in this research subject is saturated population by taking all students majoring in Business and marketing of SMK in Banyuwangi. Based on the results of the study, it is stated that entrepreneurship education can increase the online business intention of vocational students in Banyuwangi, so the better the entrepreneurship education, the better the online business intention.